The Synergy of Military and Civil Society in High-Value Timber Production: Developing Forest Institutions Above the Ruins of Conflict - Bayu Mitra A. Kusuma (Universitas Andalas, 2022)
Maluku is a province in eastern Indonesia that has experienced prolonged conflict due to racial and sectarian issues. This conflict can be resolved when the state through the military changes its approach from security to prosperity. With the synergy of the military and civil society as the basic foundation of the Green Gold program, Maluku has transformed into a producer of high-value timber such as agarwood (Aquilaria Malaccensis) and sandalwood (Santalum Album) from their production forests. This research aims to analyze the institutional governance of production forests in Maluku using the Institutional Analysis and Development (IAD) framework as an analytical tool. To analyze the above phenomenon, this research used a descriptive qualitative approach with data collected from interviews and literature studies. The research results showed that: First, in terms of Attributes of the Resource, it was found that basically local users have managed the production forest resources quite well, but they still have a high dependence on military assistance. Second, in terms of Attributes of the Users, it was found that the community has a high sense of belonging to the forest. There is an assumption that if they do not manage the forest well, it will be difficult for them to escape from conflict. Therefore, in order to realize community self-government over the forest, the military gradually reduced its role.